Influence Creativity Students and Of Job Training Experience to Work Readiness Grade XI Student Of Automatic Skill and Office Management Programs In SMK Swasta Jambi Medan Year 2020-2021 - Sri Mutmainnah (Outline Journal of Education, 2022)
This research was conducted with the aim of knowing the Effect of Student Creativity and Field Work Practices on the Work Readiness of Grade XI Students in Automation and Office Management at Private Vocational School Jambi Medan T.A 2020/2021. This research was conducted in Class XI Automation and Office Management at Jambi Medan Private Vocational High School with a total population of 93 people. Based on data analysis using the SPSS 23.00 for windows program, the hypothesis of this study was tested with the t (partial) test, it was found that student creativity had a positive and significant effect on student work readiness. then field work practice has a positive and significant effect on student work readiness. The F test (simultaneous) obtained that there was a significant influence between student creativity and field work practice on the work readiness of class XI students of Class XI Office Management Automation in Jambi Private Vocational High School, Jambi, TA 2020/2021. Furthermore, the results of the coefficient of determination of the value of R2 is 0.471, which means that the variables of student creativity and field work practice have an influence on the variable of student work readiness by 47.1%. While the remaining 52.9% is influenced by other variables that are outside the focus of this study.